Factors influencing the use of supervised delivery services in Garu-Tempane District, Ghana - John Kuumuori Ganle; Mathew Loyarl Kombet; Leonard Baatiema (BMC, 2019)
Abstract Background There is evidence that supervised delivery has the potential to improve birth outcomes for both women and newborns. However, not all women especially in low-income settings like Ghana use supervised delivery services during childbirth. The purpose of this study was to estimate the prevalence of supervised delivery and determine factors that influence use of supervised delivery services in a local district of Ghana. Methods A retrospective cross-sectional survey of 322 randomly sampled postpartum women who delivered between January and December 2016 in the Garu-Tempane District was conducted. Structured questionnaires were used to collect data. Descriptive, binary and multivariate logistic regression analysis techniques were used to analyse data. Results Although antenatal care attendance among respondents was very high 291(90.4%), prevalence of supervised birth was only 219(68%). More than a quarter 103(32%) of the postpartum women delivered their babies at home without skilled birth attendants. After controlling for possible confounders in multivariable logistic regression analyses, factors that strongly independently predicted supervised delivery were religion (p < 0.01), distance to health facility (p < 0.05), making at least 4 antenatal care visits (p < 0.01), national health insurance scheme registration (p < 0.01), satisfaction with services received during antenatal care (p < 0.01), need partner's approval before delivering in health facility (p < 0.01), woman's thoughts that her religious beliefs prohibited health facility delivery(p < 0.01), and woman's belief that there are norms in her community that did not support health facility delivery (p < 0.01). Conclusion There is need for targeted interventions, including community mobilization and health education, and male partner involvement to help generate local demand for, and uptake of, supervised delivery services. Improvement in the quality of services in health facilities, including ensuring respect and dignity for service users, would also be essential.